2021
DOI: 10.3389/fncel.2021.649262
|View full text |Cite
|
Sign up to set email alerts
|

The Theta Rhythm of the Hippocampus: From Neuronal and Circuit Mechanisms to Behavior

Abstract: This review focuses on the neuronal and circuit mechanisms involved in the generation of the theta (θ) rhythm and of its participation in behavior. Data have accumulated indicating that θ arises from interactions between medial septum-diagonal band of Broca (MS-DbB) and intra-hippocampal circuits. The intrinsic properties of MS-DbB and hippocampal neurons have also been shown to play a key role in θ generation. A growing number of studies suggest that θ may represent a timing mechanism to temporally organize m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 194 publications
2
61
0
Order By: Relevance
“…In the current study, we showed that the Ach concentration is also reduced in the hippocampus of HCNP-pp KO mice compared with Control mice. Based on our data and previous reports, there is a possibility that the reduction of theta power in HCNP-pp KO mice might be mediated through diminished Ach in the septo-hippocampal formation, which can reduce the activity of GABAergic neurons in the MSN 19 , 20 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the current study, we showed that the Ach concentration is also reduced in the hippocampus of HCNP-pp KO mice compared with Control mice. Based on our data and previous reports, there is a possibility that the reduction of theta power in HCNP-pp KO mice might be mediated through diminished Ach in the septo-hippocampal formation, which can reduce the activity of GABAergic neurons in the MSN 19 , 20 .…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, the theta activity in CA1 of the hippocampus was reduced in HCNP-pp KO mice 18 . This electrophysiological data suggest that HCNP and/or HCNP-pp is involved in generation of theta oscillations in the hippocampus, which entrains the theta oscillation of the MSN via enhanced ACh release in the medial septum and the enhanced release of ACh in the CA1 stratum oriens 19 , 20 . However, we were unable to demonstrate reduction of Ach release in the hippocampus of those mice, and alteration of cholinergic neurons in the MSN of those mice.…”
Section: Introductionmentioning
confidence: 73%
“…To assess the physiological relevance of the altered heart-brain communication, we evaluated possible behavioral adaptations in TGAC8s. In rodents, theta rhythms have been linked to locomotor activity because it plays a pivotal role in controlling initiation of the movement 49 and regulating locomotion speed 50,27,51 . Bellesi and coworkers reported that reduced EEG theta power, expressed in the frontal and parietal cortical areas of rats, increased their motor activity, especially when EEG changes were more prominent 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The cholinergic modulation of theta rhythm is well known for decades. Numerous studies have demonstrated that acetylcholine, cholinesterase inhibitors, and cholinergic agonists can induce hippocampal theta oscillation while antagonists block it (reviewed by Nuñez and Buño, 2021 ). Cholinergic induction of theta is largely mediated by the activation of M 1 mAChRs in hippocampal pyramidal neurons ( Ovsepian et al, 2004 ), although nAChRs may also play a role through the basal forebrain cholinergic projections to hippocampal interneurons ( Griguoli et al, 2010 ).…”
Section: Neuromodulationmentioning
confidence: 99%